3D Electron Microscopy Reveals Evidence for Strong Electric Fields at Nanoconfined Air–Water Interfaces - Ryota Saito; Haruka Tsuruda; Chenghui Zhu; Jianze Zhang; Xuehua Zhang; Koji Takahashi; Richard N. Zare; Xinxing Zhang; Qin-Yi Li (Journal of the American Chemical Society, 2026)
Abstract Strong electric fields at air–water interfaces are widely invoked to explain accelerated interfacial chemistry, yet direct, probe-free evidence under evaporation-free conditions has remained challenging. Here, we confine aqueous solutions and air within ∼50 nm-diameter multiwalled carbon nanotubes to stabilize nanoscale air–water interfaces for three-dimensional transmission electron microscopy. Reconstructed multiphase structures reveal ∼10 nm gas domains separated from the nanotube walls by ultrathin water films spanning molecular to nanometer thicknesses. Curvature analysis yields Laplace and disjoining pressure distributions indicating a repulsive pressure of ∼10 MPa that prevents film collapse. This repulsion is consistent with an interfacial electric field on the order of several volts per nanometer, primarily associated with oriented water dipoles and potentially enhanced by the electric double layer. Consistent with this inferred field strength, the reduction of chloroauric acid (HAuCl4) to gold nanoparticles occurs exclusively within ∼2 nm of the interface. These results provide evidence for intense, spatially confined electric fields at air–water interfaces through the combined observations of strong non-Derjaguin–Landau–Verwey–Overbeek repulsive pressures and localized interfacial Au reduction and establish their fundamental role in nanoscale interfacial chemistry across chemical, environmental, and energy-relevant systems.